Nature of Volleyball Sport, Performance Analysis in Volleyball, and the Recent Advances of Machine Learning Application in Sports - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
This chapter presents the overview, nature, and history of the volleyball sport. The chapter also highlights the performance -related parameters that contribute to the successful delivery of performance in this sport. The recent advances in the application of various machine learning models towards solving the classification and regression problems associated with the data often acquired in the sporting domain are also provided. Moreover, the detailed procedures of the participants’ recruitment, data collection techniques via performance analysis as well as various univariate statistical analyses employed to achieve the purpose of the present study have also been presented. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd